Recent advances in interface microscopic characterization of carbon fiber-reinforced polymer composites - Liu, Liting; Du, Minshu; Liu, Feng (Frontiers in Materials, 2023)
Carbon fiber reinforced polymer composites (CFRPs) have excellent properties, e.g., low density, high-temperature resistance, high specific modulus, and high specific strength, and are widely used in aerospace and civil industries. CFRP comprises carbon fiber, polymer matrix, and the interface between them. The microstructure, chemical composition, bonding mode, and interfacial bonding strength of the CFRPs interface greatly influence the mechanical properties and failure behavior of CFRPs. Accordingly, the deep, systematic and nuanced characterization of the microstructure and properties of the interfaces is one of the critical problems in the research field of CFRPs. In this paper, various microscopic characterization methods of CFRPs interface micromorphology, microstructure, chemical composition and mechanical properties developed in recent years are reviewed. For example, scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy (Raman), nanoindentation and other advanced analytical characterization techniques, as well as the application of newly developed microscopic in situ mechanical testing methods in the interface characterization of CFRPs. The prospect and trend of interface microscopic characterization technology of CFRPs have also been prospected.